Rancang Bangun Sistem Informasi Aplikasi E-Pasal Berbasis Mobile BAWASLU Kota Surabaya Menggunakan Metode Activity Centered Design (ACD): Rancang Bangun Sistem Informasi Aplikasi E-Pasal Berbasis Mobile BAWASLU Kota Surabaya Menggunakan Metode Activity Centered Design (ACD) - Wafiroh, Nabillatul; Narulita, Luvia Friska (Yayasan Nuraini Ibrahim Mandiri, 2024)
Elections, as the foundation of democracy, require effective and transparent supervision, making the role of the General Election Supervisory Agency (BAWASLU) crucial. BAWASLU Surabaya faces challenges in accessing and referencing laws and articles related to elections. To address these challenges, the development of a mobile and website information system is a relevant solution to enhance the performance of BAWASLU Surabaya. The development of this system focuses primarily on using Flutter, a mobile application development framework. The Activity-Centered Design (ACD) method, which emphasizes the primary function of the application to view laws and articles, is also applied to ensure the mobile application meets the needs of BAWASLU members with features like PDF reading, search, and bookmarking frequently used articles. The integration between the mobile application and the admin website will ensure efficient content management, including real-time updates of laws and articles. This system is expected to improve the efficiency of BAWASLU Surabaya members in meetings and election supervision, reduce dependence on physical books, and enhance the accuracy of their tasks. Additionally, system evaluation using the System Usability Scale (SUS) method will help ensure that the application meets high usability standards. Consequently, SUS evaluation will provide better insight into how well the application is accepted and used by BAWASLU Surabaya members and identify areas needing improvement to enhance the overall user experience. Keywords: Information System, API, Flutter, Mobile Application, Activity-Centered Design Method, System Usability Scale (SUS) Method